Vaccination coverage of Roma children, and barriers and attitudes of Roma parents - Ioanna Stilianesi; Pinelopi Varela; Panagiotis Mitropoulos; Anna Deltsidou (Folia Medica)
Introduction: The population of Roma children is an especially vulnerable social group, experiencing a greater prevalence of health risk factors and presenting poor vaccination rates. Aim: The objective of this study was to examine the vaccination coverage among the Roma child population in a specific prefecture of Greece and to assess the barriers and attitudes of Roma parents regarding vaccination. Materials and methods: This cross-sectional study included two hundred Roma children aged 2 to 12 years old residing in ten settlements of one prefecture in Greece. Data were collected through the use of two structured questionnaires, which consisted of questions regarding the demographic characteristics of the Roma child population, information related to vaccination, Roma settlements, and information regarding the barriers and attitudes of Roma parents about vaccination. Results: The percentage of vaccination coverage rose to 61.63%, and the majority of the children had vaccination documents. The vaccination coverage was not associated with the age of the children but their sex had an impact. The vaccination rate was greater in the larger cities, and it was also affected by the settlement. Fifty-one percent of the Roma parents did not report any difficulty regarding the vaccination of their children, and only 9% reported barriers related to financial reasons. Moreover, 21.5% of parents had insufficient information about the necessity of vaccinations, while seventeen expressed a lack of motivation. Conclusions: The present study found that the vaccination coverage among Roma children in one prefecture of Greece was low. Health professionals need to implement targeted Roma interventions considering their cultural sensitivities.